Analisis Program Bantuan Langsung Tunai (BLT) dalam Meningkatkan Kesejahteraan Masyarakat di Desa Manubar Kecamatan Sandaran - Rista Sagita; Mustatho Mustatho; Muhammad Tauhid (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research explores how the Direct Cash Transfer (BLT) program is implemented in Manubar Village, Sandaran Sub-district, as a government effort to assist low-income families. The research looked at different types of assistance, including BLT Dana Desa, Program Keluarga Harapan (PKH), and Non-Cash Food Assistance (BPNT), designed to help meet people's basic needs. The research aims to identify the types of assistance provided, evaluate how well they are implemented, and understand their impact on community welfare in areas such as the economy, education, clothing, food, and health. Using a descriptive qualitative approach, this research collected information through interviews with eight beneficiaries, observation, and documentation. The results showed that BLT significantly helped improve living standards, especially by fulfilling basic needs. From an Islamic economic perspective, the program embodies the values of social justice, honesty, and beneficence that are in line with the principles of wealth distribution in sharia. BLT is seen as a clear example of the government's role in improving community welfare in a targeted and meaningful way.